A study on the marketing mix strategies, marketing audit and marketing plan in Telekom Malaysia Berhad / Roslina Ali - Ali, Roslina (1998)
Telekom Malaysia Berhad (TMB) is not a new name in our country and it is a well-known organization in the telecommunication industry in Malaysia. Their aim is leading the way in this industry. Until now, TMB still can monopoly in the telecommunication service market, especially for the fixed line telephone service whether for residential, business company or corporate and government. However, TMB’s subscribers decreased, especially for cellular communication system since the competitors entered in the telecommunication industry like Celcom, Sapura, Binariang, Mutiara Telecom and Time Telecom. The main reason of many subscribers prefer to choose competitors’ cellular system is because they charged the lower rate than TMB besides they provide better quality of service. However, TMB cellular system has special advantage since their cellular system has the widest and largest coverage at 99 percent nationwide. So, it is also TMB’s strength in order to attract the large number of population for this system. Actually, Telekom Malaysia offered so many promotion packages like Internet Bonus Line Package, New Entrepreneur Package, Family Gets Family Package, Wira Package, SUKOM promotion and so on, but there still have many subscribers who do not know about those promotion. This is because, all of the phemplot for each